Is it tuberculosis or not? - Jamani, Nurjasmine Aida; Azih, Naimuddin (2015)
Non-tuberculous mycobacteria infection (NTM)may mimic a tuberculosis infection and could be a cause in patients with a chronic cough in primary care setting. The infrequency of NTH infection in a pulmonary tuberculosis infection can pose a dilemma in management.